Growth and dry matter partitioning in selected soybean (Glycine max L.) genotypes (Bangladesh Journal of Agricultural Research, 2015)
The experiment was conducted at the experimental site of Agronomy Department, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur during the period from January to June 2011 to evaluate twenty selected soybean genotypes in respect of growth, dry matter production and yield. Genotypic variations in plant height, leaf area index, dry matter and its distribution, crop growth rate and seed yield were observed. The plant height ranged from 40.33 to 63.17 cm, leaf area index varied from 3.01 to 8.13 at 75 days after emergence, total dry matter ranged from 12.25 to 24.71 g per plant at 90 days after emergence (DAE). The seed yield ranged from 1745 to 3640 kg per hectare. The genotypes BGM 02093, BD 2329, BD 2340, BD 2336, Galarsum, BD 2331 and G00015 yielded 3825, 3447, 3573, 3737, 3115, 3542 and 3762 kg per hectare, respectively and gave higher than others contributed by higher crop growth rate with maximum number of filled pods. Seed yield of soybean was positively related to total dry matter at 45 DAE (Y = 632.19 + 659.31X, R2= 0.46) and 60 DAE (Y= 95.335 + 405.53X, R2 = 0.48). The filled pods per plant had good relationship with seed yield (Y = 1397 + 41.85X, R2 = 0.41) than other components.Bangladesh J. Agril. Res. 40(3): 333-345, September 2015